Om Grundtvig og nutiden - Michelsen, William (Grundtvig-Studier, 1984)
On Grundtvig and the Present Time By William Michelsen This is a detailed review of Ejvind Larsen’s book The Living Word (Det levende ord, Copenhagen 1983), which is a series of essays on Grundtvig’s life and writings as seen by one of our contemporary writers. Ejvind Larsen was editor-in-chief of Information, a daily newspaper, while he was writing the book, and at the same time he was rewriting his and Ebbe Kløvedal Reich’s play on Grundtvig from 1973 into The Sweet Morning-Dream of the Heart; the play was performed by a group theatre throughout Denmark in the anniversary year. The play complements the book, among other things in its treatment of Grundtvig’s first marriage. The first 170 pages are a much enlarged revision of the author’s own book on Grundtvig and Marx from 1974, plus a chapter on Shakespeare’s influence, published in Grundtvig Studies 1973 under the title A Natural Philosopher after Grundtvig’s Heart. The last three chapters deal especially with Grundtvig’s relationship to women and are written under the strong influence of Freud and Melanie Klein. Ejvind Larsen maintains that Grundtvig was very close to his mother as long as she lived (until 1822), and in particular after 1810. Emphasis is laid on the poetry collection Little Songs (Kvædlinger, 1815), which has a poetic dedication to her and which supplies the retrospectively arranged poems with strongly self-critical notes from a strict orthodox viewpoint. Larsen actually claims that in 1810 Grundtvig “asked to be beaten into conversion” , or in other words, that his Christian breakthrough in 1810 was a masochistic self-delusion. The reviewer protests against this interpretation. Grundtvig knew he was spiritually sick at heart in the period October 1810 to spring 1811, and he himself says as much in letters and notes. But this illness was the first visible sign of the manic-depressive psychosis which later incapacitated him in 1844 and 1867 and which to a lesser degree left its mark on his psyche. Grundtvig was well aware of this, as is already clear from a letter to Christian Molbech in May 1808. It is also well-known from other writings on him (Provost Fr. Schmidt’s diaries), that his outbursts were no more violent than that in the spring of 1811 he could control them in the presence of others. Noone denies that in his meeting with Clara Bolton in 1831 and in his marriage to Marie Toft Grundtvig came to a far deeper understanding of himself than in the years following 1810. But it is untenable to reduce the recognition of the contradictory elements in Grundtvig’s attitude when his father demanded that he gave up his work in Copenhagen to become his curate, to masochistic self-delusion. Luther could not be obedient to God without being disobedient to his father. Grundtvig could not be obedient to God without at the same time being obedient to his father. The reviewer thus insists that it was a healthy self-awareness that forced Grundtvig to leave Copenhagen on January 5th and apply to the King for the position of curate to his father, even though this self-awareness was also accompanied by a depressive condition. The decisive influence of his mother’s letter six months previously is not denied, but nonetheless this was the beginning of a process of self-awareness in Grundtvig which was to last the rest of his life. The major achievement in Larsen’s book, according to the reviewer, is his treatment of the poem The Gospel of Woman (Kvinde-Evangeliet) (Grundtvig's Song-Work, Vol. I l l p. 399ff), which has sofar remained quite unnoticed. The reviewer calls it “the Gospel of the Present Time” , because it has not been able to be understood until now. The positive influence of the feminine on Grundtvig is emphasized in the book, making it an impressive and very inspiring volume, a worthwhile starting-point for a further study of Grundtvig’s life and work and a debate on the perspectives that are opened up in Grundtvig’s ideas and personal development.